Choice under uncertainty with the best and worst in mind: neo-additive capacities - Chateauneuf, Alain; Grant, Simon; Eichberger, Jürgen (Discussion paper series, 2003)
The concept of a non-extreme-outcome-additive capacity (neo-additive capacity ) is introduced. Neo-additive capacities model optimistic and pessimistic attitudes towards uncertainty as observed in many experimental studies. Moreover, neo-additive capacities can be applied easily in economic problems, aswe demonstrate by examples. This paper provides an axiomatisation of Choquet expected utility with neo-capacities in a framework of purely subjective uncertainty.
Keywords: Arbeitspapier; Graue Literatur